Composite semipermeable membrane and method for producing same

By setting an amino density gradient in the separation functional layer of the composite semipermeable membrane, and forming a cross-linked polyamide layer through interfacial polycondensation reaction, the problem of difficulty in balancing water permeability and removability in the existing technology is solved, and high water permeability and removability are achieved. Removable composite semipermeable membrane.

CN119343175APending Publication Date: 2025-01-21TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044379.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-06-02
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When the existing composite semipermeable membrane improves water permeability, the removal property will be reduced, making it difficult to achieve high water permeability and removal property at the same time.

Method used

By setting the amino density gradient in the separation function layer, inhibiting the water transparency resistance, and forming a surface aperture suitable for soluble removal. The specific implementation method includes the interface reaction on the porous support layer to form a synthetic polyanamide layer to control the cross -linked polyamide The ratio of the end amino quantity, carboxyl base, and amide.

Benefits of technology

Achieving high water and removing considerations, meet the demand for high -efficiency water separation and solubility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343175A_ABST
    Figure CN119343175A_ABST
Patent Text Reader

Abstract

The present invention provides a composite semipermeable membrane provided with a porous support layer and a separation function layer positioned on the porous support layer, the composite semipermeable membrane being provided with a first surface, which is a surface on the separation function layer side, and a second surface, which is a surface on the opposite side to the first surface, the separation function layer containing a crosslinked polyamide, in a cross section in the thickness direction of the separation function layer, the amino group density measured by a scanning transmission electron microscope (STEM) satisfies Nb / Nd < = 0.40 (wherein Nb and Nd are defined in the specification). ).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite semipermeable membrane useful for selective separation of a liquid mixture. The composite semipermeable membrane obtained by the present invention can be suitably used, for example, for desalination of seawater or brackish water. Background Art

[0002] Regarding separation of a mixture, there are various techniques for removing substances (such as salts) dissolved in a solvent (such as water). In recent years, the use of membrane separation has been expanding as a process for energy conservation and resource saving.

[0003] Membranes used in membrane separation methods include microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, etc. These membranes are used, for example, to obtain drinking water from seawater, brackish water, water containing harmful substances, etc., or to produce ultrapure water for industrial use, treat wastewater, and recover valuables.

[0004] Patent Document 1 discloses a composite semipermeable membrane having a porous supporting membrane and a separation functional layer composed of a cross-linked polyamide coated thereon as a separation membrane having high water permeability and removal performance. The separation functional layer is formed on the porous supporting membrane by a polycondensation reaction of a polyfunctional amine and a polyfunctional acyl halide.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-79372 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the demand for energy saving during operation has increased, and the water permeability of the composite semipermeable membrane needs to be further improved than before. On the other hand, when the water permeability of the composite semipermeable membrane is improved, there is a problem that the removability is reduced.

[0010] Therefore, an object of the present invention is to provide a composite semipermeable membrane having excellent water permeability and removability.

[0011] Means for solving problems

[0012] The present invention for solving the above-mentioned problems includes the following configurations [1] to

[11] .

[0013] [1] A composite semipermeable membrane comprising a porous supporting layer and a separation functional layer located on the porous supporting layer, the composite semipermeable membrane comprising a first surface on the separation functional layer side and a second surface on the opposite side of the first surface, the separation functional layer comprising a cross-linked polyamide, and in a cross section in a thickness direction of the separation functional layer, an amino group density measured by a scanning transmission electron microscope (STEM) satisfies Nb / Nd≤0.40,

[0014] Nb: amino density in region b

[0015] Nd: amino group density in region d

[0016] Regions a to e: regions obtained by dividing the cross section into five equal parts in the thickness direction of the separation functional layer, and the regions a to e are arranged from the first surface toward the second surface.

[0017] [2] The composite semipermeable membrane according to [1], wherein Nb is 1.0×10 -24 mol / nm 2 Below, and the Nd is 2.5×10 -24 mol / nm 2 above.

[0018] [3] A composite semipermeable membrane according to [1] or [2] above, wherein when the amount of terminal amino groups of the cross-linked polyamide is A, the amount of terminal carboxyl groups of the cross-linked polyamide is B, and the amount of amide groups of the cross-linked polyamide is C, C / (A+B) is greater than 1.7.

[0019] [4] The composite semipermeable membrane according to any one of [1] to [3] above, wherein the separation functional layer comprises a thin film mainly composed of a cross-linked polyamide,

[0020] The thickness of the thin film is greater than or equal to 9.0 nm and less than or equal to 13.0 nm.

[0021] [5] The composite semipermeable membrane according to any one of [1] to [4], wherein when water containing 500 ppm sodium chloride, 20 ppm silicon dioxide and 1 ppm boron is allowed to pass through the composite semipermeable membrane at an operating pressure of 0.75 MPa, the following formulas (1) to (5) are satisfied:

[0022] Silica removal rate ≥ 99.30% Formula (1)

[0023] Boron removal rate ≥ 60% Formula (2)

[0024] Water permeability ≥ 0.85m 3 / m 2 / Tianshi(3)

[0025] 99.90%>NaCl removal rate ≥99.50% Formula (4)

[0026] (NaCl removal rate) - (silicon dioxide removal rate) ≤ 0.20% formula (5).

[0027] [6] A method for producing a composite semipermeable membrane, wherein a polyfunctional amine solution containing a compound X and a polyfunctional acid halide solution containing a compound Y are brought into contact on a porous supporting layer to form a polyamide layer by an interfacial polycondensation reaction, wherein the octanol / water partition coefficients of the compound X and the compound Y satisfy the following formulas (6) to (8):

[0028] LogP(X)<0 Formula (6)

[0029] LogP(Y)<0 Formula (7)

[0030] LogP(X) / LogP(Y)<0.50 Formula (8).

[0031] [7] The method for producing a composite semipermeable membrane according to [6] above, wherein the water content in the organic solvent in which the polyfunctional acid halide is dissolved is 50 ppm or less.

[0032] [8] The method for producing a composite semipermeable membrane according to [6] or [7], wherein the polyfunctional amine solution is applied to the porous supporting layer at a surface area of ​​200 mL / m 2 Above 400mL / m 2 The polyfunctional acid halide solution in the following amount was contacted to form a polyamide layer by an interfacial polycondensation reaction.

[0033] [9] A method for producing ultrapure water, comprising a reverse osmosis step of removing silicon dioxide from a silicon dioxide-containing aqueous solution using the composite semipermeable membrane described in any one of [1] to [5] above.

[0034]

[10] The method for producing ultrapure water according to the above [9], further comprising a pretreatment step of removing suspended matter in the silica-containing aqueous solution before the reverse osmosis step.

[0035]

[11] The method for producing ultrapure water according to [9] or

[10] , further comprising a step of removing solute salts from the aqueous solution treated by the reverse osmosis step using an ion exchange resin.

[0036]

[12] A composite semipermeable membrane element comprising the composite semipermeable membrane according to any one of [1] to [5] above.

[0037]

[13] A composite semipermeable membrane module comprising the composite semipermeable membrane element described in

[12] above.

[0038] Effects of the Invention

[0039] The composite semipermeable membrane of the present invention can suppress water permeation resistance and form a surface pore size sufficient for solute removal by providing a gradient in amino group density in the membrane thickness direction of the separation functional layer, thereby achieving high water permeability and removal performance at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] [ Figure 1 ] Figure 1 This is a cross-sectional view showing a schematic structure of a composite semipermeable membrane according to one embodiment of the present invention.

[0041] [ Figure 2 ] Figure 2 It is a cross-sectional view showing the corrugated structure of the film in the separation function layer.

[0042] [ Figure 3 ] Figure 3 This is a schematic diagram for explaining the method of measuring the 10-point average surface roughness.

[0043] [ Figure 4 ] Figure 4 It is a cross-sectional view showing regions a to e in the thin film of the separation functional layer.

[0044] [ Figure 5 ] Figure 5 It is a flowchart showing the process of the method for producing ultrapure water which is one embodiment of the present invention. DETAILED DESCRIPTION

[0045] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments.

[0046] It should be noted that, in this specification, "mass" and "weight" are synonymous.

[0047] (1) Composite semipermeable membrane

[0048] The composite semipermeable membrane of the present invention comprises a porous supporting layer and a separation functional layer located on the porous supporting layer. Figure 1 As shown, in the present embodiment, the surface of the composite semipermeable membrane 1 on the separation functional layer 4 side is referred to as a first surface 11 , and the surface opposite to the first surface is referred to as a second surface 12 .

[0049] (1-1) Separation Function Layer

[0050] (1-1-1) Composition

[0051] Among the components of the composite semipermeable membrane, the separation functional layer is the one that actually has the ability to separate solutes. Figure 1 In the cross-sectional view of the composite semipermeable membrane shown, the separation functional layer 4 is disposed on the porous supporting layer 3 .

[0052] The separation functional layer contains cross-linked polyamide, and preferably contains cross-linked polyamide as a main component.

[0053] In this specification, “X contains Y as a main component” means that Y contains 50 mass % or more, 80 mass % or more, or 90 mass % or more of X, and also includes the case where X is composed of Y only.

[0054] The cross-linked polyamide refers to a polycondensate of a polyfunctional amine and a polyfunctional acid halide.

[0055] Here, the polyfunctional amine refers to an amine having at least two primary and / or secondary amino groups in one molecule, at least one of which is a primary amino group. Examples of the polyfunctional amine include polyfunctional aromatic amines such as phenylenediamine, xylenediamine, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene, 3,5-diaminobenzoic acid, 3-aminobenzylamine, and 4-aminobenzylamine, in which two amino groups are bonded to a benzene ring in an arbitrary positional relationship among ortho, meta, and para positions, or aliphatic amines such as ethylenediamine and propylenediamine, and alicyclic polyfunctional amines such as 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, 4-aminopiperidine, and 4-aminoethylpiperazine.

[0056] Among them, if the selective separation, permeability and heat resistance of the composite semipermeable membrane are taken into consideration, the polyfunctional amine is preferably a polyfunctional aromatic amine having 2 or more and 4 or less primary and / or secondary amino groups in one molecule. As such a polyfunctional aromatic amine, for example, m-phenylenediamine, p-phenylenediamine, 1,3,5-triaminobenzene, etc. are suitable for use. Among them, m-phenylenediamine (hereinafter referred to as "m-PDA") is more preferably used in view of ease of acquisition or ease of operation.

[0057] These multifunctional amines may be used alone or in combination of two or more. When two or more are used in combination, the above amines may be combined with each other or with an amine having at least two secondary amino groups in one molecule. Examples of amines having at least two secondary amino groups in one molecule include piperazine and 1,3-bispiperidinylpropane.

[0058] The polyfunctional acid halide is an acid halide having at least two halogenated carboxyl groups in one molecule. Examples of the trifunctional acid halide include trimesoyl chloride (hereinafter referred to as "TMC"), 1,3,5-cyclohexanetricarboxyl chloride, and 1,2,4-cyclobutanetricarboxyl chloride.

[0059] Examples of the bifunctional acid halide include aromatic bifunctional acid halides such as biphenyl dicarboxylic acid chloride, azophthaloyl dicarboxylic acid chloride, terephthaloyl dicarboxylic acid chloride, isophthaloyl dicarboxylic acid chloride, and naphthaloyl dicarboxylic acid chloride; aliphatic bifunctional acid halides such as adipoyl chloride and sebacoyl chloride; or alicyclic bifunctional acid halides such as cyclopentane dicarboxylic acid chloride, cyclohexane dicarboxylic acid chloride, and tetrahydrofuran dicarboxylic acid chloride.

[0060] If the reactivity with polyfunctional amine is considered, the polyfunctional acyl halide is preferably a polyfunctional acyl chloride. In addition, if the selective separation and heat resistance of the composite semipermeable membrane are considered, the polyfunctional acyl halide is preferably a polyfunctional aromatic acyl chloride with more than 2 and less than 4 phosgene groups in one molecule. Wherein, from the viewpoint of the ease of obtaining and the ease of operation, it is further preferably trimesoyl chloride. These polyfunctional acyl halides can be used alone, or more than 2 can be used simultaneously.

[0061] The separation functional layer preferably has a film with a pleated structure. The film preferably contains a cross-linked polyamide as a main component. From the viewpoint of obtaining sufficient separation performance and water permeability, the thickness of the film is preferably 8.0 nm or more, more preferably 9.0 nm or more. On the other hand, the thickness of the film is preferably 20.0 nm or less, more preferably 13.0 nm or less.

[0062] The thickness of the film with a pleated structure can be controlled, for example, by the concentration of the polyfunctional amine and polyfunctional acyl halide as monomers, the coating amount of the polyfunctional acyl halide solution relative to the surface area of ​​the porous supporting layer, etc., as described in the "separation functional layer formation process" described later.

[0063] The thickness of the film can be measured by photographing the cross section of the film with the wrinkled structure using a transmission electron microscope (hereinafter referred to as "TEM") and reading the cross section photograph into image analysis software for analysis. Specifically, in the TEM image of the cross section of the separation functional layer, any five convex portions formed in the film are selected. In one convex portion ( Figure 2 In the marks 21 and 22 in FIG. 1 , the height from the top of the convex portion to the height ( Figure 2 The thickness of the film was measured at 10 points in the area where the marks 23 and 24 in the figure are stopped. Figure 2 27). That is, Figure 2 As shown, the surface of the porous supporting layer is 0% height, the top of the protrusion is 100% height, and 10 measurement points are selected at random within the range of 10% to 100% height. The arithmetic mean value calculated from the thickness of the total 50 points thus obtained is the "thickness of the film".

[0064] Here, when calculating the thickness of the thin film, the convex portion to be measured is a convex portion having a height of one fifth or more of the 10-point average surface roughness.

[0065] The 10-point average surface roughness is calculated as follows. First, the cross section perpendicular to the film surface is observed using an electron microscope. The observation magnification is preferably 10,000 to 100,000 times. In the obtained cross-sectional image, Figure 3 As shown, the surface of the separation functional layer 4 shows a wrinkled curve with continuous and repeated convex and concave parts. For this curve, a roughness curve defined based on JIS B 0601: 2013 (ISO4287: 1997) was obtained. A cross-sectional image was extracted with a width of 2.0 μm as a reference length L in the direction of the average line X of the roughness curve.

[0066] Based on the average line of the extracted part, the sum of the average value of the absolute values ​​of the elevations of the tops from the highest peak to the fifth peak of the roughness curve (Yp1-5) and the average value of the absolute values ​​of the elevations of the bottoms from the lowest valley to the fifth valley (Yv1-5) is calculated, and the value is expressed in nanometers (nm) as the 10-point average surface roughness ( Figure 3 ).

[0067] The average line is a straight line defined in accordance with ISO 4287:1997 and is a straight line drawn so that the total area of ​​the region surrounded by the average line and the roughness curve becomes equal above and below the average line in the measurement length.

[0068] From the viewpoint of obtaining sufficient water permeability, the median value of the height of the convex portion of the separation functional layer in this embodiment is preferably 80 nm or more, more preferably 120 nm or more, and further preferably 160 nm or more. On the other hand, the median value of the height of the convex portion of the separation functional layer is preferably 300 nm or less.

[0069] The median value of the height of the convex portion is calculated as follows. For the composite semipermeable membrane, when observing any 10 cross sections, in each cross section, the height of the convex portion of more than 1 / 5 of the above-mentioned 10-point average surface roughness is measured. Furthermore, based on the calculation results of the 10 cross sections, the median value is calculated, so that the median value of the height of the convex portion can be obtained. Here, each cross section has a width of 2.0 μm in the direction of the average line of the roughness curve.

[0070] It should be noted that the convex portion refers to the space between the vertices of mutually adjacent portions (concave portions) in the thin film of the separation functional layer that protrude toward the porous supporting layer. Figure 2 As shown, one of the two ends of the protrusion (vertices of the concave portion) may be away from the surface of the porous supporting layer while the other may be in contact with the surface; either end may be in contact with the porous supporting layer or may be away from the porous supporting layer.

[0071] The height of the convex portion of the separation functional layer can be adjusted by, for example, adding an additive that interacts with the polyfunctional amine through hydrogen bonding or the like to the aqueous layer or the organic layer, or by adjusting the diffusibility of the polyfunctional amine in the organic layer.

[0072] (1-1-2) Characteristics

[0073] Regarding the composite semipermeable membrane of the present invention, in a cross section in the thickness direction of the separation functional layer (a cross section perpendicular to the first surface), the amino group density measured by a scanning transmission electron microscope (hereinafter referred to as "STEM") satisfies Nb / Nd≤0.40. Wherein, Nb represents the amino group density of region b, and Nd represents the amino group density of region d. In addition, Figure 4 As shown, each region is obtained by dividing the cross section of the separation functional layer in the thickness direction into five equal parts, and is arranged in the order of regions a to e from the first surface toward the second surface.

[0074] The separation functional layer mainly composed of cross-linked polyamide formed by interfacial polycondensation has amino and carboxyl groups as terminal functional groups. In the region with high amino density, the separation functional layer has a loose structure, low water resistance and improved water permeability, but insufficient solute removal performance. On the other hand, in the region with low amino density, the separation functional layer has a dense structure, high water resistance and low water permeability, but improved solute removal performance.

[0075] The inventors of the present application have found that, in particular, a separation functional layer having a gradient structure of amino group density satisfying Nb / Nd≤0.40 can simultaneously achieve high water permeability and removal performance. From the viewpoint of achieving both water permeability and removal performance, Nb / Nd is preferably 0.05 or more, more preferably 0.10 or more. On the other hand, Nb / Nd is preferably 0.35 or less, more preferably 0.30 or less.

[0076] As described in the "separation functional layer formation process" described later, Nb / Nd can be controlled by, for example, the type and concentration of compound X contained in the polyfunctional amine solution or compound Y contained in the polyfunctional acid halide solution, the water content contained in the organic solvent dissolving the polyfunctional acid halide, the coating amount of the polyfunctional acid chloride solution relative to the surface area of ​​the porous supporting layer, etc.

[0077] (i) Separation of regions a to e in the functional layer

[0078] The operation of immersing the composite semipermeable membrane in an aqueous solution of sodium tungstate (IV) for 7 minutes was repeated 4 times. The cross section of the separation functional layer in the composite semipermeable membrane was photographed at a magnification of 100,000 times by STEM. In the obtained image, in each convex portion of the separation functional layer (film), in any area included in 50% to 100% of its height, a reference point P was determined on the outer surface 26 of the film (the surface facing the opposite side of the porous support layer), and the normal line V0 passing through the reference point P was used as the center, and straight lines V1 and V2 parallel to the normal line V0 were drawn on both sides at intervals of 3 to 10 nm. In addition, the tangent Z1 of the outer surface of the film passing through the reference point P and the tangent Z2 of the inner surface 25 of the film (the surface on the side in contact with the porous support layer) parallel to it were drawn. Between Z1 and Z2, four straight lines that divide the interval into 5 equal parts are drawn. The areas surrounded by V1 and V2 and surrounded by Z1, Z2 and the straight lines therebetween are sequentially designated as areas a to e from the outer surface side of the film ( Figure 4 The area of ​​each region a to e is set to 5 nm. 2 Above 30nm 2 the following.

[0079] (ii) Amino group density

[0080] For the above-mentioned regions a to e, the brightness was measured by STEM. In the minimum brightness Lmin and the maximum brightness Lmax of the measured values, the area of ​​the part showing a brightness of more than {Lmin+(Lmax-Lmin) / 3} was integrated for each region. The integral value means the area of ​​the part with amino groups labeled with tungsten (W). The integral value was obtained by dividing the obtained integral value by the area of ​​each amino molecule (0.04nm 2 ), Avogadro constant (6.0×10 23 / mol) and the area of ​​each region, the amino group density (mol / nm 2 ) It should be noted that the average value of the amino group density obtained for the five convex portions of the film was taken as the amino group density of each region.

[0081] The composite semipermeable membrane of this embodiment preferably has Nb of 1.0×10 -24 mol / nm 2 Below, and Nd is 2.5×10 - 24 mol / nm 2 For a membrane with a low amino group density near the surface layer, Nb is more preferably 0.8×10 -24 mol / nm 2 Below, more preferably 0.6×10 -24 mol / nm 2On the other hand, from the viewpoint of ensuring the water permeability of the membrane, Nb is preferably 0.2×10 - 24 mol / nm 2 More preferably, 0.4×10 -24 mol / nm 2 above.

[0082] In addition, for a membrane with a high amino group density on the inner side of the separation functional layer, Nd is more preferably 2.7×10 -24 mol / nm 2 More preferably, 3.0×10 -24 mol / nm 2 On the other hand, from the viewpoint of maintaining the physical strength of the functional layer, Nd is preferably 3.5×10 -24 mol / nm 2 Below, more preferably 3.0×10 -24 mol / nm 2 the following.

[0083] As described in the "separation functional layer formation process" described later, Nb and Nd can be controlled by, for example, the type and concentration of compound X contained in the polyfunctional amine solution or compound Y contained in the polyfunctional acid halide solution, the water content contained in the organic solvent dissolving the polyfunctional acid halide, the coating amount of the polyfunctional acid chloride solution relative to the surface area of ​​the porous supporting layer, etc.

[0084] (iii) The amount of terminal amino groups A, terminal carboxyl groups B, and amide groups C of the cross-linked polyamide

[0085] The terminal amino group amount A, terminal carboxyl group amount B, and amide group amount C of the cross-linked polyamide in the composite semipermeable membrane can be determined by the separation functional layer. 13 C solid-state nuclear magnetic resonance measurement (hereinafter referred to as " 13 Specifically, after the substrate is peeled off from the composite semipermeable membrane to obtain the separation function layer and the porous support layer, the porous support layer is dissolved and removed to obtain the separation function layer. The obtained separation function layer is subjected to DD / MAS method. 13 In C solid NMR measurement, each ratio is calculated based on comparison of the integrated values ​​of the carbon peaks of each functional group or the carbon peaks to which each functional group is bonded.

[0086] From the viewpoint of improving removal performance and physical strength, the composite semipermeable membrane of the present embodiment preferably has a ratio of the amount of amide groups C of the cross-linked polyamide to the sum of the amount of terminal amino groups A and the amount of terminal carboxyl groups B (C / (A+B)) of 1.7 or more. C / (A+B) means the ratio of the amount of amide groups of the cross-linked polyamide to the amount of terminal groups. By relatively increasing the amount of amide groups serving as cross-linking points, the compactness of the membrane is improved, and the removal of solutes and the physical and chemical strength of the separation functional layer are improved. For the above reasons, C / (A+B) is more preferably 1.8 or more, and further preferably 1.9 or more. On the other hand, from the viewpoint of ensuring water permeability, C / (A+B) is preferably 2.2 or less, and more preferably 2.1 or less.

[0087] The amount A of terminal amino groups, the amount B of terminal carboxyl groups, and the amount C of amide groups of the cross-linked polyamide can be controlled by, for example, the concentrations of the polyfunctional amine and the polyfunctional acid halide as monomers or the polymerization time.

[0088] (iv) Separation characteristics

[0089] The composite semipermeable membrane of the present embodiment is suitable for separation of nonionic solutes in addition to ionic solutes such as sodium chloride, and is also characterized by differences in the removal properties of the respective solutes.

[0090] The composite semipermeable membrane of the present embodiment preferably allows the silicon dioxide removal rate of 99.30% or more, more preferably 99.45% or more when the supply water containing 500ppm sodium chloride (hereinafter referred to as "NaCl"), 20ppm nonionic silicon dioxide and 1ppm boron is passed through at an operating pressure of 0.75MPa. In addition, the boron removal rate is preferably 60% or more, more preferably 65% ​​or more. In addition, the NaCl removal rate is preferably 99.50% or more, more preferably 99.60% or more, and on the other hand, it is preferably less than 99.90%. In addition, the difference between the NaCl removal rate and the silicon dioxide removal rate is preferably 0.20% or less.

[0091] When the silica removal rate, boron removal rate, NaCl removal rate, and the difference between the NaCl removal rate and the silica removal rate are within the above ranges, high-quality permeate water can be obtained while suppressing solute concentration on the membrane surface such as scale.

[0092] Here, the removal rate of each solute is represented by 100×{1-solute concentration in permeate water / solute concentration in feed water}.

[0093] In addition, from the viewpoint of reducing the energy consumption during membrane operation, the water permeability under the above conditions is preferably 0.85 m 3 / m 2 / day or more.

[0094] (1-2) Porous Support Layer

[0095] The porous supporting layer is a base for forming the separation functional layer, and it itself does not substantially have separation performance of ions or the like.

[0096] As for the size and distribution of pores in the porous supporting layer, for example, it is preferred to have uniform and fine pores or fine pores that gradually increase in size from the surface on one side forming the separation functional layer to the surface on the other side, and the size of the fine pores on the surface on one side forming the separation functional layer is greater than 0.1 nm and less than 100 nm.

[0097] The porous supporting layer can be obtained, for example, by casting a high molecular weight polymer on a fabric, i.e., a substrate, formed of at least one selected from polyester and aromatic polyamide. The composite semipermeable membrane of this embodiment only needs to include a porous supporting layer and a separation functional layer. Figure 1 As shown, the substrate 2 and the porous supporting layer 3 disposed on the substrate 2 may be provided. In addition, hereinafter, the structure in which the porous supporting layer is formed on the substrate may be referred to as a "supporting film".

[0098] As the raw material of the porous supporting layer, for example, homopolymers or copolymers of polysulfone, polyethersulfone, polyamide, polyester, cellulose polymer, vinyl polymer, polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfone, polyphenylene ether, etc. can be used alone or in combination. As cellulose polymer, cellulose acetate, cellulose nitrate, etc. can be used, and as vinyl polymer, polyethylene, polypropylene, polyvinyl chloride, polyacrylonitrile, etc. can be used. Among them, as the raw material of the porous supporting layer, homopolymers or copolymers of polysulfone, polyamide, polyester, cellulose acetate, cellulose nitrate, polyvinyl chloride, polyacrylonitrile, polyphenylene sulfide, polyphenylene sulfide sulfone, etc. are preferred. The raw material of the porous supporting layer is more preferably cellulose acetate, polysulfone, polyphenylene sulfide sulfone or polyphenylene sulfone, and then, among these raw materials, polysulfone is usually preferably used due to high chemical stability, mechanical stability, thermal stability and easy molding.

[0099] For example, by casting a polysulfone N,N-dimethylformamide (hereinafter referred to as "DMF") solution on a densely woven polyester cloth or polyester nonwoven fabric to a certain thickness and wet-coagulating it in water, a supporting membrane can be obtained in which most of the surface has micropores with a diameter of less than 10 nm.

[0100] The thickness of the supporting film affects the strength of the composite semipermeable membrane obtained and the packing density when the composite semipermeable membrane is made into an element. From the viewpoint of obtaining sufficient mechanical strength and packing density, the thickness of the supporting film is preferably 30 μm or more, more preferably 100 μm or more. On the other hand, the thickness of the supporting film is preferably 300 μm or less, more preferably 220 μm or less.

[0101] The morphology of the porous support layer can be observed by a scanning electron microscope, a transmission electron microscope or an atomic force microscope. For example, when observing with a scanning electron microscope, the porous support layer peeled off from the substrate is cut by a freezing fracture method as a sample for cross-sectional observation. Platinum, platinum-palladium or ruthenium tetrachloride is thinly coated on the sample and observed by a high-resolution electric field emission scanning electron microscope (hereinafter referred to as "UHR-FE-SEM") at an accelerating voltage of 3 to 15 kV. UHR-FE-SEM can use an S-900 electron microscope manufactured by Hitachi, Ltd., etc.

[0102] The thickness of the porous supporting layer is preferably 20 μm or more and 100 μm or less. By making the thickness of the porous supporting layer 20 μm or more, good pressure resistance can be obtained, and a uniform supporting membrane without defects can be obtained. The composite semipermeable membrane with such a porous supporting layer exhibits good desalination performance. In addition, by making the thickness of the porous supporting layer 100 μm or less, the residual amount of unreacted substances during manufacturing can be reduced, and the reduction in water permeability and the reduction in chemical resistance can be suppressed.

[0103] (2) Manufacturing method

[0104] (2-1) Step of forming a porous supporting layer

[0105] The step of forming the porous supporting layer includes the steps of applying a polymer solution on a substrate and immersing the substrate coated with the solution in a coagulation bath to coagulate the polymer.

[0106] In the step of coating the polymer solution on the substrate, the polymer solution is prepared by dissolving the polymer, which is a component of the porous supporting layer, in a good solvent for the polymer.

[0107] Regarding the temperature of the polymer solution during the polymer solution coating, for example, when polysulfone is used as the polymer, it is preferably above 10°C and below 60°C. If the temperature of the polymer solution is within this range, the polymer will not precipitate, and the polymer solution will be fully impregnated between the fibers of the substrate and then solidified. As a result, the porous supporting layer is firmly bonded to the substrate through the anchoring effect, and a good supporting membrane can be obtained. It should be noted that the preferred temperature range of the polymer solution can be appropriately adjusted according to the type of polymer used, the desired solution viscosity, etc.

[0108] The time from the time the polymer solution is applied to the substrate until it is immersed in the coagulation bath is preferably 0.1 seconds to 5 seconds. If the time until the time of immersion in the coagulation bath is within this range, the organic solvent solution containing the polymer is fully impregnated between the fibers of the substrate and then solidified. It should be noted that the preferred range of the time until the time of immersion in the coagulation bath can be appropriately adjusted according to the type of polymer solution used, the desired solution viscosity, etc.

[0109] As a coagulation bath, water is usually used, but it is not particularly limited as long as it does not dissolve the polymer as a component of the porous support layer. Depending on the composition of the coagulation bath, the membrane morphology of the obtained support membrane changes, and the composite semipermeable membrane obtained thereby also changes. The temperature of the coagulation bath is preferably above -20°C and below 100°C, and more preferably above 10°C and below 50°C. If the temperature of the coagulation bath is within this range, the vibration of the coagulation bath surface caused by thermal motion will not become intense, and the smoothness of the membrane surface after the membrane is formed is maintained. In addition, if the temperature is within this range, the coagulation speed is appropriate and the film-forming property becomes good.

[0110] Next, the obtained supporting film is washed with hot water in order to remove the residual solvent in the film. The temperature of the hot water is preferably 40°C to 100°C, more preferably 60°C to 95°C. If the temperature of the hot water is within this range, the shrinkage of the supporting film will not increase, and the water permeability will be good. In addition, if the temperature of the hot water is within this range, a sufficient washing effect can be obtained.

[0111] (2-2) Separation Function Layer Formation Step

[0112] The method for producing a composite semipermeable membrane of the present embodiment is a method for producing a composite semipermeable membrane in which a polyfunctional amine solution containing a compound X and a polyfunctional acyl halide solution containing a compound Y are brought into contact on a porous supporting layer to form a polyamide layer through an interfacial polycondensation reaction, wherein the octanol / water partition coefficients of the compound X and the compound Y satisfy the following formulas (6) to (8).

[0113] LogP(X)<0···Formula (6)

[0114] LogP(Y)<0···Formula (7)

[0115] LogP(X) / LogP(Y)<0.50···Formula (8)

[0116] Wherein, LogP(X) refers to the octanol / water partition coefficient of compound X, and LogP(Y) refers to the octanol / water partition coefficient of compound Y.

[0117] Preferred embodiments of the polyfunctional amine and the polyfunctional acid halide are the same as those described above. Hereinafter, the process will be described by taking as an example the case where a polyfunctional aromatic amine is used as the polyfunctional amine and a polyfunctional aromatic acid chloride is used as the polyfunctional acid halide.

[0118] As an organic solvent for dissolving the polyfunctional aromatic acyl chloride, any solvent that is immiscible with water, does not damage the supporting membrane, and does not hinder the formation reaction of the cross-linked aromatic polyamide can be used. As a representative example, halogenated hydrocarbons such as liquid hydrocarbons and trichlorotrifluoroethane can be cited. If it is considered that it is a substance that does not damage the ozone layer, the ease of obtaining, the ease of operation and the safety in operation, it is preferred to use single substances such as octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, heptadecane, hexadecane, cyclooctane, ethylcyclohexane, 1-octene, 1-decene or their mixtures.

[0119] The aqueous solution containing the polyfunctional aromatic amine contains a compound X having an octanol / water partition coefficient of less than 0, the organic solvent dissolving the polyfunctional aromatic acid chloride contains a compound Y having the same octanol / water partition coefficient of less than 0, and the ratio of the octanol / water partition coefficients of the compound X to the compound Y, LogP(X) / LogP(Y), is less than 0.50. By making LogP(X) / LogP(Y) satisfy this range, the compound X and the compound Y are appropriately mixed at the interface during polymerization, and an intermediate layer that promotes the polymerization reaction is stably formed, thereby forming a polyamide separation functional layer with high separation performance.

[0120] On the other hand, when LogP(X) / LogP(Y) is 0.50 or more, the compound X or the compound Y is unlikely to migrate, so that it is difficult to form an intermediate layer that promotes the polymerization reaction and it is difficult to form a polyamide separation functional layer with high separation performance.

[0121] Examples of the compound X and the compound Y include compounds having a polyoxyalkylene structure, a fatty acid structure, an amide structure, an ether structure, a sulfone group, or a hydroxyl group.

[0122] Examples of the polyoxyalkylene structure include -(CH2CH2O) n -、-(CH2CH2(CH3)O) n -、-(CH2CH2CH2O) n -、-(CH2CH2CH2CH2O) n -wait.

[0123] Examples of the fatty acid structure include fatty acids having a long-chain aliphatic group. The long-chain aliphatic group may be linear or branched, and examples thereof include salts of stearic acid, oleic acid, lauric acid, and palmitic acid.

[0124] Examples of the compound having a sulfonic group include salts of 1-hexanesulfonic acid, 1-octanesulfonic acid, 1-decanesulfonic acid, 1-dodecanesulfonic acid, perfluorobutanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, and octylbenzenesulfonic acid.

[0125] Examples of the compound having a hydroxyl group include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, glycerol, sorbitol, glucose, and sucrose.

[0126] Examples of the amide compound include N-methylformamide, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-diethylacetamide, N-methylpyrrolidone, γ-butyrolactam, and ε-caprolactam.

[0127] Examples of the compound having an ether structure include ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol diacetate, diethylene glycol dibenzoate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, diethylene glycol bis(p-toluenesulfonic acid), diethylene glycol bis(3-aminopropyl) ether, 1,2-bis(2-aminoethoxy)ethane, dipropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and tetraethylene glycol diethyl ether.

[0128] In order to carry out interfacial polycondensation on the porous supporting layer, first, the surface of the porous supporting layer is coated with an aqueous solution of a polyfunctional aromatic amine. The concentration of the polyfunctional aromatic amine in the aqueous solution of the polyfunctional aromatic amine is preferably 0.1 mass % to 20 mass %, more preferably 0.5 mass % to 15 mass %.

[0129] In order to fully form the intermediate layer and suppress the disorder of the intermediate layer to stably form the separation functional layer, the concentration of the compound X is preferably 0.1 mass % to 10 mass %, more preferably 0.5 mass % to 5 mass %.

[0130] As a method for coating the surface of the porous support layer with an aqueous solution of a polyfunctional aromatic amine, as long as the surface of the porous support layer is uniformly and continuously coated with the aqueous solution, known coating means can be cited, such as a method of coating the aqueous solution on the surface of the porous support layer, a method of immersing the porous support layer in the aqueous solution, etc. The contact time between the porous support layer and the aqueous solution of the polyfunctional aromatic amine is preferably from 5 seconds to 10 minutes, and more preferably from 10 seconds to 3 minutes. Next, it is preferred to remove the over-coated aqueous solution through a deliquescence process. As a method for deliquescence, for example, a method of keeping the membrane surface in a vertical direction and allowing it to flow down naturally can be cited. After deliquescence, the membrane surface is dried to remove all or part of the water in the aqueous solution.

[0131] Then, the polyfunctional aromatic acid chloride solution is applied onto the porous supporting layer coated with the polyfunctional aromatic amine aqueous solution to form a cross-linked aromatic polyamide by interfacial polycondensation.

[0132] In the manufacture method of the composite semipermeable membrane of the present embodiment, the water content contained in the organic solvent dissolving the multifunctional acyl halide is preferably below 50ppm. By reducing the moisture in the organic solvent, it is possible to suppress the hindrance of the polycondensation reaction of the multifunctional amine and the multifunctional acyl halide by moisture, and it is possible to form a suitable surface pore size. For the above reasons, the water content in the organic solvent dissolving the halide is more preferably below 30ppm. In addition, by making the water content in the organic solvent dissolving the multifunctional acyl halide below 50ppm, it is possible to suppress the hindrance of the polymerization reaction, and highly maintain the compactness of the surface layer of the separation function layer. Thus, it is easy to manufacture a separation function layer in which the amide group density Nb near the surface layer of the separation function layer is small and the amide group density Nd on the inner layer side is large.

[0133] The water content in the organic solvent can be measured by the Karl Fischer titration method described in JIS K0068: 2001. The Karl Fischer method includes volumetric titration and coulometric titration, and the coulometric titration is suitable for the analysis of trace amounts of water in the organic solvent.

[0134] In the method for producing a composite semipermeable membrane of the present embodiment, it is preferred that the polyfunctional amine solution and the surface area of ​​the porous supporting layer be 200 mL / m 2 Above 400mL / m 2 The following amount of polyfunctional acid chloride solution was contacted to form a crosslinked polyamide layer by interfacial polycondensation. The amount of polyfunctional acid chloride solution applied was set to 200 mL / m2 relative to the surface area of ​​the porous supporting layer. 2 Above 400mL / m 2 When the ratio is within the following range, the intermediate layer has an appropriate ratio, the interfacial polymerization reaction proceeds appropriately, and a separation functional layer having a desired amide group density or thickness can be produced.

[0135] The time for carrying out the interfacial polycondensation is preferably from 0.1 second to 3 minutes, and more preferably from 0.1 second to 1 minute.

[0136] The concentration of the polyfunctional aromatic acid chloride in the polyfunctional aromatic acid chloride-containing solution is not particularly limited, but is preferably 0.01 mass % or more and 1.0 mass % or less from the viewpoint of sufficient formation of the separation functional layer and from the viewpoint of cost.

[0137] In addition, from the viewpoint of fully achieving the formation of the intermediate layer and suppressing the disorder of the intermediate layer to stably form the separation functional layer, the concentration of compound Y is preferably 0.01 mass % to 1.0 mass %, and more preferably 0.02 mass % to 0.5 mass %.

[0138] Next, the organic solvent remaining after the reaction is preferably removed by a liquid removal step. As the removal of the organic solvent, for example, the film can be held in a vertical direction to remove the excess organic solvent by naturally flowing down. In this case, the holding time in the vertical direction is preferably more than 1 minute and less than 5 minutes, and more preferably more than 1 minute and less than 3 minutes. By making the holding time more than 1 minute, it is easy to obtain a cross-linked aromatic polyamide with a target function, and by making it less than 5 minutes, it is possible to suppress the generation of defects caused by excessive drying of the organic solvent, thereby suppressing performance degradation.

[0139] (3) Utilization of composite semipermeable membrane

[0140] The composite semipermeable membrane of this embodiment is wound around a cylindrical water collecting pipe having a plurality of holes together with raw water flow path materials such as plastic nets, permeated water flow path materials such as tricot, and a membrane for improving pressure resistance as needed, and can be used as a spiral composite semipermeable membrane element. In addition, the element can also be connected in series or in parallel and housed in a pressure vessel to form a composite semipermeable membrane assembly.

[0141] In addition, the composite semipermeable membrane, its elements, and modules can be combined with a pump for supplying raw water to them, a device for pre-treating the raw water, etc., to form a fluid separation device. By using this separation device, raw water can be separated into permeated water such as drinking water and concentrated water that has not permeated the membrane, thereby obtaining water that meets the purpose.

[0142] From the viewpoint of improving the salt removal rate and membrane permeation flux, the feed water temperature of the fluid separation device is preferably 5° C. to 45° C. In order to suppress the generation of scale such as magnesium and suppress membrane degradation, it is preferable to operate at a feed water pH in the neutral range.

[0143] The component using the composite semipermeable membrane of this embodiment is characterized by high separation of nonionic solutes, and is particularly suitable for introduction into processes such as ultrapure water production processes for semiconductor manufacturing, where ultrapure water is produced from raw water containing extremely small amounts of organic matter and silicates.

[0144] (3-1) Ultrapure water production method

[0145] like Figure 5As shown, the method for producing ultrapure water described below includes: a pretreatment step for removing suspended matter from raw water; a primary treatment step (reverse osmosis step) containing a reverse osmosis membrane for removing silica from the aqueous solution after the above-mentioned pretreatment step; and a secondary treatment step for removing ion components from the aqueous solution passing through the above-mentioned step containing a reverse osmosis membrane.

[0146] It should be noted that the ultrapure water production method according to the present embodiment requires only the reverse osmosis step, and the other steps are optional.

[0147] (3-2) Pre-treatment process

[0148] (3-2-1) Raw water

[0149] The supply water (raw water) used as the object in this embodiment is an aqueous solution containing silicon dioxide (aqueous solution containing silicon dioxide), and specifically, for example, river water, groundwater, wastewater recovery water, cooling water return water, etc. Silica is mostly present in the form of silicates, and its charge state changes according to the change of the pH of the raw water, but it is not easy to be charged in the neutral range (pH6-8). In addition, boric acid also changes its charge state according to the change of the pH of the raw water, but it is not easy to be charged in the neutral range (pH6-8).

[0150] (3-2-2) Pretreatment method

[0151] The method for producing ultrapure water of the present embodiment preferably includes a pretreatment step for removing suspended matter in the aqueous solution containing silica before the primary treatment step (reverse osmosis step) described later. Suspended matter contained in raw water may cause clogging (scaling) when adhering to the reverse osmosis membrane surface of the primary treatment step in the later stage. Therefore, by passing a part or all of the raw water through an MF membrane (microfiltration membrane) or a UF membrane (ultrafiltration membrane) for filtration treatment (pretreatment) and then supplying it to the primary treatment step, scaling can be suppressed.

[0152] (3-3) Primary treatment process (reverse osmosis process)

[0153] (3-3-1) Reverse Osmosis Membrane (RO Membrane)

[0154] The method for producing ultrapure water of the present embodiment includes a reverse osmosis step of removing silicon dioxide from an aqueous solution containing silicon dioxide using the composite semipermeable membrane of the present embodiment. That is, the method for producing ultrapure water of the present embodiment includes a step of separating and removing silicon dioxide from raw water or an aqueous solution treated in a pre-treatment step using the composite semipermeable membrane of the present embodiment as a reverse osmosis membrane in a primary treatment step.

[0155] The composite semipermeable membrane of the present embodiment used as a reverse osmosis membrane preferably has removal and water permeation characteristics satisfying the following equations (1) to (3) when water containing 500 ppm NaCl, 20 ppm silica, and 1 ppm boron is passed through at an operating pressure of 0.75 MPa.

[0156] Silica removal rate ≥ 99.30%···Formula (1)

[0157] Boron removal rate ≥ 60% Formula (2)

[0158] Water permeability ≥ 0.85m 3 / m 2 / day···Formula (3)

[0159] Surprisingly, it is found that the composite semipermeable membrane of the present embodiment is not easy to reduce the silica removal rate even when it is contacted with an oxidant such as an aqueous solution of hypochlorous acid used as a chemical for washing the UF membrane in the pretreatment process and washing the pipe dirt, and has a high selective separation. Although the details of the reason are unclear, sodium hypochlorite enlarges the size of the fine pores in the pore structure of the reverse osmosis membrane that help remove boric acid, thereby improving the permeability of water. On the other hand, it is believed that by maintaining a pore size larger than boric acid and smaller than silica, the permeability ratio of water to silica is maintained, thereby having the effect of suppressing the reduction of the silica removal rate and reducing the silica concentration in the permeated water.

[0160] In addition, due to the high permeability, it is possible to operate at a high recovery rate without increasing the operating pressure to reduce the amount of concentrated water (waste water), and realize a highly efficient process.

[0161] Furthermore, by using the composite semipermeable membrane of this embodiment that satisfies the following formulas (4) and (5), the load on the subsequent secondary treatment step can be reduced, a highly efficient process can be achieved, and the generation of silica scale on the membrane surface can be suppressed, which is preferred.

[0162] 99.90%>NaCl removal rate≥99.50%···Formula (4)

[0163] (NaCl removal rate) - (Silicon dioxide removal rate) ≤ 0.20% ···Formula (5)

[0164] The details of the above-mentioned action are unclear, but the following mechanism can be considered. When filtering an aqueous solution containing silica and other ions, the components removed on the surface of the reverse osmosis membrane are concentrated on the membrane surface and become highly concentrated. The solubility of silica in water at 25°C is usually 120 mg / L. When the solubility is exceeded, it precipitates and covers the surface of the reverse osmosis membrane as scale, which becomes a filtration resistance and causes a decrease in water permeability. On the other hand, the solubility of silica decreases as the surrounding ion concentration increases. Therefore, it is believed that when the sodium chloride removal rate is high, the total concentration of sodium chloride and other ions concentrated on the membrane surface increases locally, and the silica concentrated on the membrane surface also exceeds the solubility and precipitates, forming scale to cover the surface of the reverse osmosis membrane, and the water permeability decreases.

[0165] In addition, when the value obtained by subtracting the silica removal rate from the NaCl removal rate is greater than 0.20%, the full picture of the details is not clear, but it is believed that due to the large unevenness in the membrane structure that affects the removal performance, parts with high removal performance and parts with low removal performance are mixed. In the part with high removal performance, the sodium chloride concentration on the membrane surface becomes high and the solubility of silica decreases, thereby generating silica scale, causing filtration resistance and easily reducing water permeability.

[0166] (3-3-2) Operation method

[0167] It is preferred that raw water or a pre-treated aqueous solution be supplied to the reverse osmosis membrane within a pressure range of 0.10 MPa to 12 MPa. If the pressure is above 0.10 MPa, the decrease in the membrane permeation rate of water can be suppressed. If it is below 12 MPa, the possibility of affecting membrane damage can be reduced. In addition, if the pressure is supplied at a pressure of 0.25 MPa to 6 MPa, the membrane permeation flux is high, so the aqueous solution can be efficiently permeated, and the possibility of affecting membrane damage is small. Therefore, it is more preferred, and particularly preferred, to supply at a pressure of 0.25 MPa to 1 MPa. The water permeability of the reverse osmosis membrane is 0.85m 3 / m 2 / day or more, sufficient water permeability can be obtained even in low-pressure operation such as 1MPa or less, which can reduce energy consumption and water production cost per unit of water production. In addition, it is possible to design an equipment based on a small-scale pump, which can save space.

[0168] The primary treatment process may be a multi-stage treatment, that is, the aqueous solution after pre-treatment may be filtered through the first reverse osmosis membrane, and the permeate obtained may be treated again through the second reverse osmosis membrane. In addition, in order to reduce the discarded water and improve the recovery rate, the concentrated water obtained by filtering through the first reverse osmosis membrane may be treated through the second reverse osmosis membrane.

[0169] (3-4) Secondary treatment process

[0170] The method for producing ultrapure water of this embodiment preferably further includes a step of removing solute salts from the aqueous solution treated by the reverse osmosis step using an ion exchange resin. That is, it preferably includes a secondary treatment step of further removing ion components from the aqueous solution as permeate obtained by the primary treatment step to produce ultrapure water. The secondary treatment step preferably uses an ion exchange resin (ion exchanger).

[0171] As a method of using ion exchange resins, an ion exchange device including a cation exchange resin and an anion exchange resin can be used, or an electrical regeneration deionization (hereinafter referred to as "EDI") can be used. EDI is a device having a desalination chamber divided by an ion exchange membrane and filled with an ion exchanger, a concentration chamber for concentrating the ions desalted by the desalination chamber, and an anode and a cathode for passing an electric current. It is a device that simultaneously performs a deionization (desalination) treatment of the treated water using the ion exchanger and a regeneration treatment of the ion exchanger by passing an electric current. The treated water passed into the EDI is desalinated by the ion exchanger filled in the desalination chamber and discharged to the outside of the EDI as EDI treated water. Similarly, the concentrated water in which the ions are concentrated is discharged to the outside as EDI concentrated water.

[0172] Furthermore, UV treatment may be included as a secondary treatment step. If the silica concentration of the aqueous solution supplied in the primary treatment step is high, silica precipitates on the surface of the ion exchange resin in the secondary treatment step, causing a decrease or degradation in the treatment efficiency of the secondary treatment step.

[0173] Example

[0174] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited to these Examples at all.

[0175] [1. Measurement of characteristics]

[0176] (Water content of organic solvent in interfacial polycondensation)

[0177] The measurement was performed by Karl Fischer coulometric titration using a trace water content measuring apparatus (CA-200 manufactured by Mitsubishi Chemical Analytech Co., Ltd.).

[0178] (NaCl removal rate, silica removal rate, boron removal rate)

[0179] The composite semipermeable membrane was supplied with a temperature of 25°C, a pH of 7, and water adjusted to 500ppm of sodium chloride, 87ppm of sodium metasilicate (20ppm in terms of silicon dioxide), and 5.7ppm of boric acid (1ppm in terms of boron) at an operating pressure of 0.75MPa for membrane filtration treatment. The conductivity of the supply water and the permeate water was measured with a conductivity meter (CM-41X manufactured by Toa Denpa Kogyo Co., Ltd.) to obtain their respective practical salinities, i.e., NaCl concentrations. The NaCl removal rate was calculated based on the following formula according to the obtained NaCl concentration. Among them, the NaCl concentration (ppm) refers to the concentration based on the mass standard.

[0180] NaCl removal rate (%) = 100 × {1-(NaCl concentration in permeate water / NaCl concentration in feed water)}

[0181] The silica concentration and boron concentration of the feed water and the permeated water were measured by an ICP emission spectrometer (5110VDV manufactured by Agilent), and the silica removal rate and the boron removal rate were calculated according to the following formula.

[0182] Silica removal rate (%) = 100 × {1-(silica concentration in permeate water / silica concentration in feed water)}

[0183] Boron removal rate (%) = 100 × {1-(boron concentration in permeate water / boron concentration in feed water)}

[0184] (Water permeability)

[0185] In the above test, the membrane permeability of the supplied water was measured, and the value converted into the permeability (cubic meters) per square meter of membrane surface per day was taken as the permeability (m 3 / m 2 / sky).

[0186] (Preparation of amino density measurement sample)

[0187] The 5 cm square composite semipermeable membrane obtained after physical peeling of the substrate was processed by cryo-ultra-thin sectioning, placed on a grid, immersed in pure water for 4 hours, and then immersed in a 10 mass % 2-propanol aqueous solution for 1 hour for washing. Then, the sample was immersed in 1.0×10 Na2WO4·2H2O adjusted to pH 3.8 and 25°C for a total of 3 times. -3 The sample was immersed in a 1.0×10 mol / L aqueous solution for 10 minutes, and then immersed in 1.0×10 -7 The sample was immersed in a mol / L aqueous solution for 7 minutes. Then, the sample was dehydrated with filter paper and freeze-dried to obtain a sample for amino density measurement.

[0188] (Amino density)

[0189] The composite semipermeable membrane sample prepared in the previous item was photographed using a field emission transmission electron microscope (HF5000 manufactured by Hitachi High-Tech) at an accelerating voltage of 200 kV to obtain a STEM image at a magnification of 100,000. The obtained image was then analyzed using image processing software, and the amino group density was calculated for each region a to e based on the brightness value and by the method described in the above "(ii) Amino group density".

[0190] (Terminal amino group amount A, terminal carboxyl group amount B, amide group amount C)

[0191] From composite semipermeable membrane 5m 2 Physically peel off the substrate and recover the porous supporting layer and the separation functional layer. After standing at 25°C for 24 hours to dry, add small amounts gradually to a beaker filled with dichloromethane and stir to dissolve the polymer constituting the porous supporting layer, and recover the insoluble matter in the beaker with filter paper. Add the insoluble matter to a beaker filled with dichloromethane and stir to recover the insoluble matter in the beaker. Repeat this operation until the polymer forming the porous supporting layer can no longer be detected to be eluted into the dichloromethane solution. The recovered separation functional layer is dried with a vacuum dryer to remove residual dichloromethane. The obtained separation functional layer is made into a powdered sample by freeze-crushing, sealed in a sample tube for solid NMR measurement, and subjected to CP / MAS and DD / MAS methods. 13 C solid state NMR determination. 13 For C solid NMR measurement, CMX-300 manufactured by Chemagnetics was used. The measurement conditions were as follows.

[0192] Standard substance: polydimethylsiloxane (internal standard: 1.56ppm)

[0193] Sample speed: 10.5kHz

[0194] Pulse repetition time: 100s

[0195] From the obtained spectrum, peaks derived from carbon atoms bonded to the respective functional groups are segmented, and the functional group amount ratio is quantified from the areas of the segmented peaks.

[0196] (NaCl removal rate after contact with sodium hypochlorite aqueous solution)

[0197] A reverse osmosis membrane (10 cm×10 cm) was immersed in 5 L of an aqueous solution of sodium hypochlorite adjusted to 10 mg / L and pH 7 and maintained at 25° C. for 96 hours. Then, the NaCl removal rate was measured by the method described in the above “NaCl removal rate, silica removal rate, and boron removal rate”.

[0198] When the NaCl removal rate after contact with the sodium hypochlorite aqueous solution was 98.90% or more, it was judged that the resistance to the performance reduction due to the contact with sodium hypochlorite was good.

[0199] (Silica scale adhesion amount)

[0200] The feed water was treated by membrane filtration using the method described in the above “NaCl removal rate, silica removal rate, and boron removal rate”, and the total water permeability reached 100 L / m 2 The composite semipermeable membrane was used to extract the deposits on the membrane surface with a 1% by mass nitric acid aqueous solution, and the total adsorption amount (mg) of the silica component was measured using an ICP emission analyzer (5110VDV manufactured by Agilent). The silica scale attachment amount (mg / m 2 ).

[0201] The amount of silica scale attached is less than 0.2 mg / m 2 The case of is judged that the degree of silica scale being less likely to be generated is good.

[0202] [2. Preparation of composite semipermeable membrane]

[0203] (Comparative Example 1)

[0204] At 25°C, a polyester nonwoven fabric made of long fibers (air permeability 2.0 cc / cm 2 A 15.0 mass % DMF solution of polysulfone was cast on the support membrane, and the support membrane was immediately immersed in pure water and left for 5 minutes to prepare a support membrane with a porous support layer thickness of 40 μm. Next, the support membrane was immersed in a 2.0 mass % m-PDA aqueous solution, and the excess aqueous solution was removed. Then, a solution prepared in a manner to give a TMC concentration of 0.10 mass % was applied to the support membrane at a rate of 300 mL / m 2 Next, in order to remove excess solution from the membrane, the membrane was vertically dehydrated, dried by blowing 25°C air with a blower, and then washed with 80°C pure water to obtain a composite semipermeable membrane of Comparative Example 1.

[0205] (Comparative Example 2)

[0206] At 25°C, a polyester nonwoven fabric made of long fibers (air permeability 2.0 cc / cm 2 / s) was poured with a 15.0 mass % DMF solution of polysulfone, and immediately immersed in pure water and left for 5 minutes, thereby preparing a supporting membrane with a porous supporting layer thickness of 40 μm. Next, the supporting membrane was immersed in an aqueous solution of 2.0 mass % m-PDA and 1.5 mass % dipropylene glycol (hereinafter referred to as "DPG": octanol / water partition coefficient is -1.50) as compound X, and the excess aqueous solution was removed. Then, using n-decane with a water content of 40 ppm, a solution prepared in a manner such that the concentration of TMC becomes 0.10 mass % and the concentration of N,N-dimethylacetamide (hereinafter referred to as "DMAc": octanol / water partition coefficient is -0.77) as compound Y becomes 0.1 mass % was applied to 300 mL / m 2 Next, in order to remove excess solution from the membrane, the membrane was vertically dehydrated, dried by blowing 25°C air with a blower, and then washed with 80°C pure water to obtain a composite semipermeable membrane of Comparative Example 2.

[0207] (Comparative Example 3)

[0208] The composite semipermeable membrane of Comparative Example 3 was obtained by the same method as Comparative Example 2, except that compound X was replaced by 1.0 mass% of ethylene glycol dimethyl ether (hereinafter referred to as "EGDME": octanol / water partition coefficient is -0.21), and compound Y was replaced by 0.1 mass% of diethylene glycol methyl ether (hereinafter referred to as "DEGMEE": octanol / water partition coefficient is -0.10).

[0209] (Comparative Example 4)

[0210] A composite semipermeable membrane of Comparative Example 4 was obtained by the same method as in Comparative Example 2 except that Compound X was changed to 1.5 mass % of DMAc and Compound Y was changed to 0.1 mass % of EGDME.

[0211] (Comparative Example 5)

[0212] A composite semipermeable membrane of Comparative Example 5 was obtained by the same method as Comparative Example 2 except that Compound X was replaced by 1.0 mass% EGDME and Compound Y was replaced by 0.1 mass% diethylene glycol dimethyl ether (hereinafter referred to as "DEGDME": octanol / water partition coefficient: -0.36).

[0213] (Comparative Example 6)

[0214] A composite semipermeable membrane of Comparative Example 6 was obtained by the same method as Comparative Example 2, except that Compound X was replaced by 1.2 mass % of DEGMEE and Compound Y was replaced by 0.1 mass % of diethylene glycol ethyl ether acetate (hereinafter referred to as "DEGEEAc": octanol / water partition coefficient: 0.24).

[0215] (Comparative Example 7)

[0216] At 25°C, a polyester nonwoven fabric made of long fibers (air permeability 2.0 cc / cm 2 A 15.0 mass % DMF solution of polysulfone was cast on the support membrane ( / s), and the support membrane was immediately immersed in pure water and left for 5 minutes to prepare a support membrane with a porous support layer thickness of 40 μm. Next, the support membrane was immersed in an aqueous solution of 2.0 mass % m-PDA and 1.5 mass % DPG as compound X, and the excess aqueous solution was removed. Then, a solution prepared in a manner to give a TMC concentration of 0.10 mass % was applied to the support membrane at a rate of 300 mL / m 2 Next, in order to remove excess solution from the membrane, the membrane was vertically dehydrated, dried by blowing 25°C air with a blower, and then washed with 80°C pure water to obtain a composite semipermeable membrane of Comparative Example 7.

[0217] (Comparative Example 8)

[0218] At 25°C, a polyester nonwoven fabric made of long fibers (air permeability 2.0 cc / cm 2 A 15.0 mass % DMF solution of polysulfone was cast on the support film, and the support film was immediately immersed in pure water and left for 5 minutes to prepare a support film with a porous support layer thickness of 40 μm. Next, the support film was immersed in a 2.0 mass % m-PDA aqueous solution, and the excess aqueous solution was removed. Then, a solution prepared in a manner that the TMC concentration was 0.10 mass % and the DMAc concentration as compound Y was 0.1 mass % was applied to 300 mL / m 2 Next, in order to remove excess solution from the membrane, the membrane was vertically dehydrated, dried by blowing 25°C air with a blower, and then washed with 80°C pure water to obtain a composite semipermeable membrane of Comparative Example 8.

[0219] (Comparative Example 9)

[0220] A composite semipermeable membrane of Comparative Example 9 was obtained by the same method as in Comparative Example 8 except that Compound Y was changed to 0.1 mass % of DEGEEAc.

[0221] (Example 1)

[0222] A composite semipermeable membrane of Example 1 was obtained by the same method as in Comparative Example 2, except that Compound X was replaced by 1.2 mass % of DEGMEE and Compound Y was replaced by 0.1 mass % of DEGDME.

[0223] (Example 2)

[0224] A composite semipermeable membrane of Example 2 was obtained in the same manner as in Comparative Example 2 except that Compound X was replaced by 1.0 mass % of EGDME and Compound Y was replaced by 0.03 mass % of γ-butyrolactam (octanol / water partition coefficient: -0.71).

[0225] (Example 3)

[0226] The composite semipermeable membrane of Example 3 was obtained by the same method as Comparative Example 2, except that compound X was replaced by 1.4 mass% of ε-caprolactam (octanol / water partition coefficient: -0.19) and compound Y was replaced by 0.02 mass% of N-methylformamide (hereinafter referred to as "NMF": octanol / water partition coefficient: -0.97).

[0227] (Example 4)

[0228] A composite semipermeable membrane of Example 4 was obtained by the same method as Comparative Example 2, except that Compound X was replaced by 1.2 mass % of DEGMEE and Compound Y was replaced by 0.1 mass % of diethylene glycol diacetate (hereinafter referred to as "DEGAc": octanol / water partition coefficient: -0.49).

[0229] (Example 5)

[0230] A composite semipermeable membrane of Example 5 was obtained by the same method as in Example 4 except that an n-decane solution having a water content of 20 ppm was used.

[0231] (Example 6)

[0232] Change the coating amount of n-decane solution to 180mL / m 2 , except for this, the composite semipermeable membrane of Example 6 was obtained by the same method as Example 4.

[0233] (Example 7)

[0234] Change the coating amount of n-decane solution to 420 mL / m 2 , except for this, the composite semipermeable membrane of Example 7 was obtained by the same method as Example 4.

[0235] (Example 8)

[0236] A composite semipermeable membrane of Example 8 was obtained by the same method as in Example 7 except that an n-decane solution having a water content of 70 ppm was used.

[0237] The structures of the composite semipermeable membranes obtained by Comparative Examples 1 to 9 and Examples 1 to 8 are shown in Table 1, and the performances are shown in Table 2.

[0238] [Table 1]

[0239] [Table 2]

[0240] Thus, the membranes of Examples 1 to 8 in which Nb / Nd is 0.40 or less are membranes that simultaneously achieve high water permeability and removal performance. -24 mol / nm 2 Below and Nd is 2.5×10- 24 mol / nm 2 The above films result in particularly high performance.

[0241] The preferred embodiments of the present invention are described above, but the present invention is not limited to the above embodiments, and various deformations and substitutions may be applied to the above embodiments without departing from the scope of the present invention. This application is based on Japanese patent application (Japanese patent application 2022-090653) filed on June 3, 2022, and its contents are introduced herein as a reference.

[0242] Description of Reference Numerals

[0243] 1 Composite semipermeable membrane

[0244] 2. Substrate

[0245] 3. Porous support layer

[0246] 4 Separation functional layer

[0247] 11. The first side of the composite semipermeable membrane

[0248] 12 The second side of the composite semipermeable membrane

[0249] 21 convex part i

[0250] 22 convex part ii

[0251] 23 Height of convex part i

[0252] 24 Height of convex portion ii

[0253] 25 Inner surface of the film

[0254] 26 Outer surface of the film

[0255] 27 Film thickness

[0256] X-Roughness curve average line

[0257] Yp1~5 The elevation of the fifth mountain top from the highest mountain top to X

[0258] Yv1~5 The elevation of the fifth valley bottom from the lowest valley bottom to X

[0259] L Base length

[0260] P Reference point

[0261] V0 Normal line passing through reference point P

[0262] V1, V2 are straight lines parallel to the normal V0

[0263] Z1 Tangent line of the outer surface of the film passing through the reference point P

[0264] Z2 Tangent to the inner surface of the film parallel to the tangent line Z1

Claims

1. A composite semipermeable membrane comprising a porous supporting layer and a separation functional layer located on the porous supporting layer, The composite semipermeable membrane comprises a first surface on the separation functional layer side and a second surface on the opposite side of the first surface. The separation function layer contains cross-linked polyamide, In a cross section in the thickness direction of the separation functional layer, the amino group density measured by a scanning transmission electron microscope (STEM) satisfies Nb / Nd≤0.40, Nb: amino density in region b Nd: amino group density in region d Regions a to e: regions obtained by dividing the cross section into five equal parts in the thickness direction of the separation functional layer, and the regions a to e are arranged from the first surface toward the second surface.

2. The composite semipermeable membrane according to claim 1, wherein The Nb is 1.0×10 -24 mol / nm 2 Below, and the Nd is 2.5×10 -24 mol / nm 2 above.

3. The composite semipermeable membrane according to claim 1 or 2, wherein When the amount of terminal amino groups of the cross-linked polyamide is A, the amount of terminal carboxyl groups of the cross-linked polyamide is B, and the amount of amide groups of the cross-linked polyamide is C, C / (A+B) is 1.7 or more.

4. The composite semipermeable membrane according to claim 1 or 2, wherein The separation functional layer has a thin film mainly composed of cross-linked polyamide. The thickness of the thin film is greater than or equal to 9.0 nm and less than or equal to 13.0 nm.

5. The composite semipermeable membrane according to claim 1 or 2, wherein When water containing 500 ppm sodium chloride, 20 ppm silicon dioxide, and 1 ppm boron is allowed to pass through the composite semipermeable membrane at an operating pressure of 0.75 MPa, the following equations (1) to (5) are satisfied: Silica removal rate ≥ 99.30% Formula (1) Boron removal rate ≥ 60% Formula (2) Water permeability ≥ 0.85m 3 / m 2 / Tianshi(3) 99.90%>NaCl removal rate ≥99.50% Formula (4) (NaCl removal rate) - (silicon dioxide removal rate) ≤ 0.20% formula (5).

6. A method for producing a composite semipermeable membrane, wherein: A polyfunctional amine solution containing compound X and a polyfunctional acid halide solution containing compound Y are brought into contact with each other on the porous supporting layer to form a polyamide layer by an interfacial polycondensation reaction. The octanol / water partition coefficients of the compound X and the compound Y satisfy the following formulas (6) to (8): LogP(X)<0 Formula (6) LogP(Y)<0 Formula (7) LogP(X) / LogP(Y)<0.50 Equation (8).

7. The method for producing a composite semipermeable membrane according to claim 6, wherein: The water content in the organic solvent in which the polyfunctional acid halide is dissolved is 50 ppm or less.

8. The method for producing a composite semipermeable membrane according to claim 6 or 7, wherein: The multifunctional amine solution is added to the porous supporting layer at a surface area of ​​200 mL / m 2 Above 400mL / m 2 The polyfunctional acid halide solution in the following amount was contacted to form a polyamide layer by an interfacial polycondensation reaction. 9 . A method for producing ultrapure water, comprising a reverse osmosis step of removing silicon dioxide from a silicon dioxide-containing aqueous solution using the composite semipermeable membrane according to claim 1 .

10. The method for producing ultrapure water according to claim 9, wherein: Prior to the reverse osmosis step, a pretreatment step of removing suspended matter in the silica-containing aqueous solution is also included.

11. The method for producing ultrapure water according to claim 10, wherein: The method further includes a step of removing solute salts from the aqueous solution treated by the reverse osmosis step using an ion exchange resin.

12. A composite semipermeable membrane element comprising the composite semipermeable membrane according to claim 1 or 2.

13. A composite semipermeable membrane module comprising the composite semipermeable membrane element according to claim 12.

Citation Information

Patent Citations

  • Production of polyamide reverse osmosis composite membrane

    JP2001079372A

  • Wheels and vehicles

    JP2022090653A